Fabrication of a sponge-like protein based hydrogel incorporating fluconazole against Candida species as a potential treatment for vulvovaginal candidiasis infection - Mohammad Hashem Hashempur; Ali Radmanesh; Forough Karami; Kamiar Zomorodian; Neda Amirzadeh; Sara Shenavari; Zahra Zareshahrabadi (Scientific Reports)
Abstract Vulvovaginal candidiasis is a common fungal infection in the reproductive age group of women with an estimated 70–75% of women infected at least once in their life cycle. A chronic condition, recurrent vulvovaginal candidiasis, significantly affects the quality of life in women globally. Hydrogel-based wound dressing has emerged as effective choices for wound closure, as they can mimic the structure and physicochemical properties of the extracellular matrix. However, they are frequently linked with limited biocompatibility, and a deficiency in antifungal activities. Herein, a biocompatible composite sponge-like hydrogel with effective antifungal activities is developed for the management of such wound infections. Synthesis and characterization of a sponge-like protein based hydrogels comprising keratin, gelatin (Kr/Gel), and fluconazole (Kr/Gel@Flu) were engineered via a cryogelation process. The formulation was cross-linked by sodium alginate as a cross-linker. The physicochemical properties of the hydrogels were characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray. Additional physicochemical characterizations involved its moisture content (3.70 ± 0.83% Kr/Gel@Flu), water vapor transmission rate (1438 g/m2/per day for Kr/Gel@Flu), porosity (a porosity value of 76% in the Kr/Gel@Flu), and release (21.61% release of Flu from Kr/Gel@Flu within the first 360 min) properties. The hydrogels demonstrated a fibrous structure with appropriate moisture content, indicating its potential for maintaining wound environment. The formulation exhibited significant antifungal, and antibiofilm properties also supported normal skin fibroblast and HeLa cell lines growth in vitro that confirmed their biocompatibility. In conclusion, sponge-like hydrogel combines the advantages of targeted antifungal delivery, antibiofilm activity, and biocompatibility, making it a promising candidate for biomedical applications.